2010
DOI: 10.1021/ef9011752
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Biodiesel Production from Soybean Oil Using Ultrasonics

Abstract: Our objective was to determine the effect of ultrasonics on biodiesel production from soybean oil. In this study, ultrasonic energy was applied in two different modes: pulse and continuous sonication. Soybean oil was mixed with methanol and a catalytic amount of sodium hydroxide, and the mixture was sonicated at three levels of amplitude (60, 120, and 180 μm pp ) in pulse mode (5 s on/25 s off). In the continuous mode, the same reaction mixture was sonicated at 120 μm pp for 15 s. The reaction was monitored fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 23 publications
3
36
0
5
Order By: Relevance
“…A 93.5% of biodiesel yield was obtained at a reaction time of 0.5 min under pulse conditions which can be compared to the 92% yield obtained during 3 h reaction time using 5 wt.% CaO catalyst under conventional heating and stirring, although this is a heterogeneous catalyst [43]. Our observations were found to be similar to those by Chand et al [41]. They studied a comparison on pulse and continuous mode operations.…”
Section: Effect Of Reaction Timesupporting
confidence: 84%
See 1 more Smart Citation
“…A 93.5% of biodiesel yield was obtained at a reaction time of 0.5 min under pulse conditions which can be compared to the 92% yield obtained during 3 h reaction time using 5 wt.% CaO catalyst under conventional heating and stirring, although this is a heterogeneous catalyst [43]. Our observations were found to be similar to those by Chand et al [41]. They studied a comparison on pulse and continuous mode operations.…”
Section: Effect Of Reaction Timesupporting
confidence: 84%
“…Unlike pulse sonication, the yields obtained from continuous sonication increased from 0.5 min to 1 min but started to decrease when 1.5 min was reached. According to Chand et al [41], continuous ultrasound irradiations are not recommended for long reaction times because it could affect the biodiesel yield. Similar observation was made in our study as well.…”
Section: Effect Of Reaction Timementioning
confidence: 99%
“…Chand et al observed similar improvements in heat transfer and reaction time applying ultrasonication to soybean oil transesterification. 270 However, both groups employed a homogeneous NaOH catalyst, hindering product purification. Ultrasound was used with a heterogeneous catalyst for continuous biodiesel production from palm oil by Salamatinia et al 271 BaO and SrO catalysts were tested, and ultrasound again found to reduce the reaction times and catalyst loadings needed to achieve 495% FAME yields.…”
Section: Influence Of Reactor Design and Operating Conditionsmentioning
confidence: 99%
“…270 The origin of ultrasonic enhancements in respect of reaction mixing via e.g. cavitation or microstreaming, remains a matter of debate.…”
Section: View Article Onlinementioning
confidence: 99%
“…Synthesis of Al(HSO 4 ) 3 . (Chand et al, 2010). The temperature range employed was 50-500°C at a ramp rate of 10°C/min.…”
Section: Product Analysis and Specificationsmentioning
confidence: 99%